Essential Oils of the Aerial Parts of Hypericum apricum Kar. and Kir. and Hypericum davisii Robson (Guttiferae) Species from Turkey - Bagci, Eyup; Yuce, Ebru (Asian Journal of Chemistry, 2010)
In this study, essential oil composition of Hypericum apricum Kar. and Kir. and H. davisii Robson species grown in Turkey were determined by using GC and GC-MS system. The essential oils obtained by hydrodistillation from the aerial parts of plants. Forty-two compounds were identified in the essential oils of H. apricum; a -pinene (22.2 %), caryophyllene oxide (8.0 %), nonacosane (6.3 %), b-myrcene (5.9 %) and nonane (5.9 %) (as the major). Thirty compounds were identified in the essential oils of H. davisii; nonacosane (23.8 %), a-pinene (17.8 %), caryophyllene oxide (9.5 %) and b-caryophyllene (4.4 %) (as the major). Distribution of the major compounds in essential oil were discussed among the Hypricum genus patterns.